Desafíos y riesgos como promotores de buena enseñanza en profesores memorables - Trueba, Sebastián Adolfo (Educación y Ciudad, 2019)
The present article is derived from a biographical-narrative research on the good teaching of memorable teachers in the city of Mar del Plata, Argentina. It highlights sensitive aspects of teacher training, barely visible but very powerful for the training of teachers. It emphasizes the importance of taking risks in such a challenging career as teaching, based on the narratives of the four memorable teachers of the study in question. The registration of good teaching experiences based on a polyphonic narrative construction can constitute a substantial contribution to the current teacher training agenda.